SURVEI KADAR HEMOGLOBIN PADA ATLET BULUTANGKIS DI KOTA BATU DAN KOTA MALANG - Tety Dwi Jayanti Subagio; Rias Gesang Kinanti; Olivia Andiana (Universitas Negeri Malang, 2017)
Abstract: Badminton sport in Indonesia has placed it self as a very popular sport among the society, because of the achievements achieved and able to compete with other countries in the world. Consequences of achievements that have been achieved is every player is required to always achieve optimal performance. The process of coaching in sports can not be done instantly, all the concept of a well-structured exercise should be balanced with the physiological function and the ability of erythrocytes to circulate oxygen throughout the body tissues so that all metabolic processes in sports become better and balanced.Keywords: Hemoglobine, Badminton